2022
DOI: 10.3390/plants11131782
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thymus vulgaris L. Hydrolate Solutions on the Seed Germination, Seedling Length, and Oxidative Stress of Some Cultivated and Weed Species

Abstract: The aim of this study was to determine the effect of the hydrolates obtained as the by-products of the Thymus vulgaris essential oil steam distillation process. The bioassays, which were undertaken in order to determine the effect on germination and initial growth of seedlings of some cultivated and weed species, were performed under controlled conditions with different concentrations of the hydrolates. Seeds of Glycine max, Helianthus annuus, Zea mays, Triticum aestivum, Daucus carota subsp. sativus, Allium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…A list of identified chemical components in the hydrolates used in this study is shown in Table 1. Some dominant compounds of the nine selected hydrolates were already reported, such as T. vulgaris hydrolate (TV) with thymol (73.6%), which is the same as the extent in the study of Konstantinović et al [51]; in SS hydrolate, linalool (63.3%) and α-terpineol (26.8%) were reported in the study of Aćimović et al [16]. In addition, the main component in SM hydrolate was carvacrol (96.4%) [52], while in LI hydrolate, it was linalool (26.0%), borneol (24.4%), 1,8-cineole (12.7%), and terpinen-4-ol (12.2%) [15].…”
Section: Chemical Composition Of Vocs In Hydrolatessupporting
confidence: 77%
“…A list of identified chemical components in the hydrolates used in this study is shown in Table 1. Some dominant compounds of the nine selected hydrolates were already reported, such as T. vulgaris hydrolate (TV) with thymol (73.6%), which is the same as the extent in the study of Konstantinović et al [51]; in SS hydrolate, linalool (63.3%) and α-terpineol (26.8%) were reported in the study of Aćimović et al [16]. In addition, the main component in SM hydrolate was carvacrol (96.4%) [52], while in LI hydrolate, it was linalool (26.0%), borneol (24.4%), 1,8-cineole (12.7%), and terpinen-4-ol (12.2%) [15].…”
Section: Chemical Composition Of Vocs In Hydrolatessupporting
confidence: 77%
“…A manifestação dos aleloquímicos pode influenciar a germinação, mas seus efeitos são mais notáveis no crescimento radicular, conforme observado por outros pesquisadores (BALIČEVIĆ et al, 2014;KONSTANTINOVIĆ et al, 2014).…”
Section: Discussionunclassified
“…26,27,28,29 Additionally, hydrolates have potential applications in organic agriculture as biopesticides. 30,31 The purpose of this research was to characterize volatile organic compounds from essential oil and hydrolate obtained by steam distillation of dry plant material of industrial hemp cultivar "Helena" (low THC content). In vitro antimicrobial and antioxidant activity testing was also conducted to find additional value for these products.…”
Section: Introductionmentioning
confidence: 99%